Review Jurnal: Aktivitas Deodorant Spray Ekstrak Herbal Pada Bakteri Staphylococcus sp dengan Metode Difusi Agar - Sahira Madliya, Juliettania; Rahmawati, Adelia; Ihsani, Salfia; Maelaningsih, Firdha Senja (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Body odor is induced by the secretion of sweat glands and bacterial activity. One way to overcome body odor is by maintaining proper body hygiene and using topical preparations such as antiperspirants and deodorants. This study aims to review several journal articles regarding herbal deodorant spray formulations against Staphylococcus bacteria based on the active compound concentration. The literature review was conducted by searching scientific articles published in the last 10 years from 2013 to 2023 using scientific databases. Methods: Several formulation methods have been identified in the reviewed articles including disc diffusion, paper disc diffusion, and agar diffusion methods. The active compounds tested were “kemangi” leaf extract, orange peel extract, and red ginger extract. Results: Showed that increasing the concentration of the active compounds was generally proportional to the increase in antibacterial activity. The optimal concentrations giving good antibacterial activity were 15% for orange peel extract, 8% for “kemangi” leaf extract, and 80% for red ginger extract. Conslusion: This review concludes that herbal extracts have the potential to develop as natural deodorant ingredients and the concentration of active compounds strongly influences the antibacterial activity. Keywords: Herbal extract, Concentration, Antibacterial activity, Test method, Positive and negative controls.